Dialektika Status Wanita dalam Pembaharuan Hukum Keluarga di Indonesia - Roykhatun Nikmah (UIN Raden Mas Said Surakarta, 2020)
the status of women in family law became the main focus in legal reform. The reforms made must be dynamic and flexible in the face of changes in the socio-cultural context of society. The purpose of reform in addition to raising the status of women in the relationship between husband and wife also aims to provide legal certainty. Marriage Law and the Compilation of Islamic Law as the basis for resolving matters within the Court must continue to adapt to the social shift of society and the demands of social change so as not to lose its function as a social operator. To see the change in the status of women before the existence of Law Number 1 of 1974 and also KHI then the approach used is a historical approach. The juridical approach is used to see how the rules in Law No. 1/1974 and KHI apply to adapt to the demands of society change. The focus of juridical studies on the age limit of marriage, polygamy and divorce. Determination of the age limit of marriage has changed from 16 years of age for girls to 19 years. There is a change in article 7 paragraph (1) so that women and men have a passion for the right to education, health and constitutional rights. While the rules of Indonesian polygamy are not completely prohibited but the court provides strict conditions to do, while the rules of divorce for women have the right to file for divorce if the husband violates talaq ta’liq and commits the causes of divorce.